2010
DOI: 10.3310/hta14340-04
|View full text |Cite
|
Sign up to set email alerts
|

The impact of illness and the impact of school closure on social contact patterns.

Abstract: . It provides the framework through which the research staff and research infrastructure of the NHS in England is positioned, maintained and managed as a national research facility.The NIHR provides the NHS with the support it needs to conduct first-class research funded by the Government and its partners alongside high-quality patient care, education and training. Its aim is to support outstanding individuals (both leaders and collaborators), working in world-class facilities (both NHS and university), conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 61 publications
2
73
0
1
Order By: Relevance
“…The findings on contact patterns shown in Eames et al and Kerckhove et al [96,97], combined with studies showing that prolonged viral shedding correlated with more severe disease [98,99], also suggest that a virulence-transmission trade-off exists for influenza, akin to the one for HIV mentioned above. Additional data would be needed to confirm and further quantify this potential trade-off.…”
Section: Host Behaviourmentioning
confidence: 80%
“…The findings on contact patterns shown in Eames et al and Kerckhove et al [96,97], combined with studies showing that prolonged viral shedding correlated with more severe disease [98,99], also suggest that a virulence-transmission trade-off exists for influenza, akin to the one for HIV mentioned above. Additional data would be needed to confirm and further quantify this potential trade-off.…”
Section: Host Behaviourmentioning
confidence: 80%
“…One of the few studies of this phenomenon in humans was based on self-completed written questionnaires administered by mail to 179 Britons diagnosed with swine flu [12]. That study, which focused on the measurement of contacts suitable for influenza transmission, showed that illness reduced contacts by approximately 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying the impacts of illness on direct contacts [12,13] was a significant advance for understanding the epidemiology of influenza and other directly transmitted pathogens. Nonetheless, there remain a number of gaps in knowledge about the impacts of illness on contact that merit additional study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies that have estimated the changes in contact patterns during school holidays. 70 However, prolonged school closures may lead to wider differences in contact patterns that, to our knowledge, have not been rigorously studied. Further research may well be required to inform how the contact matrix would differ from that of school holiday periods.…”
Section: Incorporating Interventionsmentioning
confidence: 98%